Interspeech 2017 2017
DOI: 10.21437/interspeech.2017-1194
|View full text |Cite
|
Sign up to set email alerts
|

Big Five vs. Prosodic Features as Cues to Detect Abnormality in SSPNET-Personality Corpus

Abstract: This paper presents an attempt to evaluate three different sets of features extracted from prosodic descriptors and Big Five traits for building an anomaly detector. The Big Five model enables to capture personality information. Big Five traits are extracted from a manual annotation while Prosodic features are extracted directly from the speech signal. Two different anomaly detection methods are evaluated: Gaussian Mixture Model (GMM) and One-Class SVM (OC-SVM), each one combined with a threshold classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…[13] found that predicting EX using classifiers trained only on the male, female, or journalist subgroups resulted in higher accuracies than all of these groups combined. [14] demonstrated features based on psychological information can bring more information to personality perception than audio features only. Despite this progress, SPC's potential has not been fully exploited due to its small size.…”
Section: Personality Perception Using Spcmentioning
confidence: 99%
“…[13] found that predicting EX using classifiers trained only on the male, female, or journalist subgroups resulted in higher accuracies than all of these groups combined. [14] demonstrated features based on psychological information can bring more information to personality perception than audio features only. Despite this progress, SPC's potential has not been fully exploited due to its small size.…”
Section: Personality Perception Using Spcmentioning
confidence: 99%
“…The choice for the different statistical models tested in this paper is driven by speaker identification and emotion recognition techniques: Gaussian Mixture Models (GMM) and Support Vector Machines (SVM). However, direct speech samples can also be considered as outliers among narrative samples and outlier detection techniques [23] such as one-class models, are also considered.…”
Section: Discourse Modelsmentioning
confidence: 99%
“…Studies were not limited only to the acoustic and nonverbal features extraction. The lexical [8], [16], knowledge-based features [14], and BFI questionnaire scores [17] were added to this variety of features as well. The effort toward achieving a wider variety of features reached 6,373 statistical feature in [18].…”
Section: Introductionmentioning
confidence: 99%